Administrative Reform: Issues of Ethics and Governance in Malaysia and China - LooSee Beh (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2007)
This paper seeks to develop an understanding of the issues that public administrators should strive to provide in ethical practices and governance thus allowing distinctive administrative and social traditions that each country possess to flourish. Significant changes and continuities in the realm of government in contemporary China and Malaysia will be drawn upon. Recent developments have brought a sense of urgency in contrast to complacency with the status quo. This paper reviews pertinent administrative and ethic issues related to both countries and whether the administrators engage in sustaining the reform agenda while still maintaining the professional capacity and flexibility of administrators when re-delegating responsibly within changing institutional settings. public administration, state, policy, administrative reforms, governance
hdl:10398/7413
Keywords: 330